Pengaruh Teknik Relaksasi Nafas Dalam terhadap Penurunan Nyeri Dismenore - Yuni Handayani; Herlidian Putri; Yusy Septyane Nurita (Jurnal MID-Z (MIDWIFERI ZIGOT), 2022)
Dysmenorrhea is a pain experienced during menstruation which is quite severe which can interfere with daily activities. Dysmenorrhea can be experienced by women who have higher intrauterine pressure and have twice as many prostaglandin levels as women who do not experience dysmenorrhea. The incidence of dysmenorrhea that occurs in the world is quite large, where the average exceeds 50%, where women in each country are found to have dysmenorrhea. Meanwhile, in Indonesia alone, it is estimated that 55% of productive women with dysmenorrhea disrupt their activities. Desminorrhea pain can be treated with non-pharmacological therapy, one of which is deep breathing relaxation techniques. Where this technique can increase pulmonary ventilation, increase oxygenation in the blood, reduce pain intensity and suppress feelings of anxiety. The purpose of this study was to determine the effect of deep breathing relaxation techniques on reducing dysmenorrhea pain in adolescent girls at SMAN 5 Jember. This study uses a quasi-experimental approach with a one-group pre-test and post-test design approach. The population is 70 young women. The sample is 60 young women with sampling using simple random sampling technique. The results showed no pain 45.0%, mild pain 41.7%, moderate pain 13.3%. The analysis test used the Wilcoxon signed rank test with p-value = 0.000 < = 0.05. The conclusion in this study is that there is an effect of deep breathing relaxation techniques on reducing dysmenorrhea pain in adolescent girls. The results of this study are expected for young women at SMAN 5 Jember to be able to do deep breathing relaxation techniques when experiencing dysmenorrhea.